WUJUD KESANTUNAN MENOLAK DALAM BAHASA BANJAR - NFN Jahdiah (Multilingual, 2014)
This study has objective to describe the form of politeness of refusal the Banjar language. It uses qualitative method. The data are obtained mainly from speech which are obtained from field notes, field records and interview :There are three steps on data analyzing. (1) data reduction, (2)data presentation, and (3)conclusion. All steps are performed during and after data collecting. Thisstudy results refusing speech acts. The Banjar language are formed imperative and declarativesentence.